(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The paper highlights specificities of occupational language of military sports cadets and postgraduates during their content-based English learning instruction. The use of diverse technologies and methods is imperative for developing cadets’ linguistic competence for effective communication. A closed group of occupational lexical units presenting part of national language is analyzed within the framework of linguodidactics. The content of certain lexico-semantic groups of military sports terms applied in occupational communication is considered. The practical significance of language experience acquired in the educational process in achieving high results in occupational activity has been identified. Key words: occupational language, communication, linguodidactics, linguistic personality, language for specific purposes, lexical and semantic group. DOI 10.18522/1995-0640-2020-3-171-175